Using fairy tales to improve the reading skill in the seventh grade students at unidad educativa fiscal Ficoa de Montalvo - Galarza Palma, Luis Angel (2015)
The main purpose of this research project is to determine the reasons why there is a low performance in the reading area in the seventh grade students at Unidad Educativa Fiscal Ficoa de Montalvo. A careful study was conducted to find and analyze those reasons after a careful revision of studies and published material developed by theorists and linguists about the reading skill. All the information was gathered through an investigation that included class observations, interviews to teachers and authorities and a survey to students…..